Novel GC-MS/MS Technique Reveals a Complex Steroid Fingerprint of Subclinical Hypercortisolism in Adrenal Incidentalomas - Hána, Václav; Ježková, Jana; Kosák, Mikuláš; Kršek, Michal; Hána, Václav; Hill, Martin (The Journal of clinical endocrinology and metabolism, 2019)
CONTEXT: Improvement of imaging methods has led to more incidental adrenal tumor findings, especially adenomas. Routine hormonal evaluation uses only a few steroids to evaluate possible hormonal hypersecretion of these adenomas, but a wide spectrum of serum steroid hormone changes has not been published. OBJECTIVE: To measure the serum levels of 83 steroids from patients with unilateral and bilateral adrenal incidentalomas to uncover full steroid profile changes in patients with subclinical hypercortisolism (SH). DESIGN: Cross-sectional study. SETTING: The study was conducted at a tertiary inpatient clinic. PATIENTS: Fifty-two patients with adrenal incidentalomas (unilateral, n = 29; bilateral, n = 23), including nonfunctioning (n = 11) vs SH (n = 41), and 26 age- and sex-matched controls from the general population were included. MAIN OUTCOME MEASURES: Eighty-three serum steroids were measured by gas chromatography-tandem mass spectrometry (GC-MS/MS) before and after 1 mg dexamethasone, ACTH, midnight serum cortisol, and urinary free cortisol/24 hour. RESULTS: Of 83 measured steroids, 10 were significantly decreased in patients with SH, including dehydroepiandrosterone sulfate (DHEAS), androsterone sulfate, epiandrosterone sulfate, androstenediol sulfate, conjugated 5α-androstane-3β,17β-diol, and conjugated 5α-androstane-3α,17β-diol. This finding was observed even when unilateral, bilateral, male, and female subgroups were analyzed separately. When we compared routine clinical methods and GC-MS/MS‒measured steroids, the most discriminatory was DHEAS followed by midnight serum cortisol, epiandrosterone sulfate, androsterone sulfate, ACTH, and 16α-hydroxypregnenolone. CONCLUSIONS: SH was associated with decreased levels of adrenal androgens, their metabolites, and pregnenolone metabolite. GC-MS/MS is a powerful tool for measuring serum levels of these undescribed changes in steroid metabolism, which are characteristic of SH in adrenal incidentalomas.
Keywords: Steroids; Cross-Sectional Studies; tandemová hmotnostní spektrometrie; plynová chromatografie s hmotnostně spektrometrickou detekcí; Adrenocortical Hyperfunction; Humans; lidé středního věku; Middle Aged; mužské pohlaví; adrenokortikální hyperfunkce; Gas Chromatography-Mass Spectrometry; nádory nadledvin; průřezové studie; steroidy; ženské pohlaví; lidé; Male; Tandem Mass Spectrometry; Adrenal Gland Neoplasms; Female